Re-opening exercise science laboratories and testing during the Covid-19 endemic phase - Dengel, D. R.; Evanoff, N. G. (International Journal of Sports Medicine, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has forced primary/grade schools and university closings as well as forced the suspension of a number of medical and laboratory testing procedures. Exercise science laboratories whether in clinical, research or educational locations were also forced to pause testing procedures. As the COVID-19 pandemic begins to subside in some areas of the world, exercise science laboratories are contemplating how to create a safe environment to resume some laboratory testing activities. In this article, we present suggestions for how exercise science laboratories can open and create a safe environment for subjects, laboratory personnel and equipment upon reopening.